The Theoretical Aspects to the Introduction of “Smart” Technologies Into the Activities of Local Self-Government Bodies - Maliukhov, Oleksandr (Theory and Practice of Public Administration, 2019)
The theoretical aspects of implementation of “smart” technologies in the activities of local self-government bodies were considered during the research. A number of scientific achievements of domestic and foreign researchers have been systematized, in which the approaches to the emergence of the “smart city” phenomenon are substantiated. It is determined that the statement has a historical connection with the concepts of “smart community” and “intelligent city”. The initiatives on implementation of “smart” technologies in the city management system, which are approved by the European Union, have been researched. Also, the definition of “smart city”, as a complex and multifunctional local system, is considered from the side of the public administration. The priority direction of development of the “smart city” is to improve the quality of life of the city’s inhabitants and to ensure the safety of the environment.It is obvious that the processes of proper implementation of “smart” technologies anticipate the effective use of intelligent automated control system in the activities of local self-government bodies. Through continuous monitoring, public authorities have the opportunity to identify timely the problematic aspects, analyze and optimize the conditions of the life and activities of citizens. In this case, the main thing is to create special conditions for the development of cities, which, by increasing their competitiveness, will ensure the uniformity of economic and social development of the state’s territories.Prospects of further exploration in this direction are the formation and substantiation of a coherent system of new quality of the relationship between city dwellers and public authorities that leads to changes in priorities, system of goals, tasks, ways of their solution, indicators of completeness of realization of goals and effectiveness of their achievement.